Extended-Spectrum Beta-Lactamase-Producing Escherichia coli in Feces and Wastewater Treatment System in Swine Farms, Thailand - Yossapol, Montira; Jinawa, Panutchada; Kaowanan, Pumipat; Thanapratpruang, Tharaporn; Sonrit, Sarawut; Konputtar, Adithep; Laoseeyong, Benjawan; Odoi, Justice Opare (Trends in Sciences, 2023)
The antimicrobial resistance (AMR) problem is one that demands urgent interventions to minimize the rapid spread in humans, animals and the environment. Extended-spectrum beta-lactamase-producing Escherichia coli (ESBL-Ec) could spread from livestock farms to environment or circulate in farms via wastewater. This study aimed to quantify and characterize ESBL-Ec in swine feces and wastewater samples collected from 2 conventional swine farms with wastewater treatment systems. Microbiological analysis was performed on fecal and wastewater samples, and the concentration of cefotaxime (CTX)-resistant bacteria, indicative of ESBL-Ec, was determined across different stages of wastewater treatment. Additionally, ESBL-Ec was isolated and identified from fresh feces, swine house wastewater, and treated wastewater from covered lagoons and photosynthetic ponds. Results indicated a higher concentration of CTX-resistant bacteria in the wastewater in the early process of wastewater treatment. However, CTX-resistant bacteria were not detected in the final photosynthetic pond in one of the 2 farms. ESBL-Ec was identified in fresh feces from swine houses and wastewater treatment plants in both farms. Further antimicrobial susceptibility testing revealed diverse resistance patterns among the ESBL-Ec isolates, with tetracycline and gentamicin demonstrated the highest resistance rates. The ESBL genes identified belonged to the CTX-M-14, CTX-M-17 and CTX-M-55. This study demonstrated the presence of ESBL-Ec in swine feces and wastewater, emphasizing the importance of effective wastewater treatment before discharging to limit the spread of AMR bacteria. HIGHLIGHTS ESBL producers was isolated from fecal and wastewater samples from swine farms The wastewater treatment system could reduce cefotaxime-resistant bacteria CTX-M-14, CTX-M-17 and CTX-M-55 genes were detected in swine farms, Thailand GRAPHICAL ABSTRACT